2004
DOI: 10.1038/sj.bdj.4811476
|View full text |Cite
|
Sign up to set email alerts
|

'It's difficult being a dentist': stress and health in the general dental practitioner

Abstract: Objective The aim of the study was to investigate overall stress, workstress and health in general dental practitioners (GDPs). Design, setting and subjects A nationwide anonymous crosssectional survey was undertaken using stratified random sampling of 2,441 GDPs in the UK. Main outcome measures Measures included perceived stress, Work Stress Inventory for Dentists, job dissatisfaction, measures of health symptoms and health behaviour, dental and demographic information. Results The main findings were that per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
169
9
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(208 citation statements)
references
References 9 publications
22
169
9
8
Order By: Relevance
“…[38][39][40] A profound sense of overwhelm and exhaustion, particularly emotional exhaustion, and professional stress are also very common among dentists. [41][42][43] One explanation could be that patients learn to dislike their dentists as they come to associate them with fear. Consequently, dental work is often unwelcome and unappreciated.…”
Section: Dentist Dissatisfactionmentioning
confidence: 99%
“…[38][39][40] A profound sense of overwhelm and exhaustion, particularly emotional exhaustion, and professional stress are also very common among dentists. [41][42][43] One explanation could be that patients learn to dislike their dentists as they come to associate them with fear. Consequently, dental work is often unwelcome and unappreciated.…”
Section: Dentist Dissatisfactionmentioning
confidence: 99%
“…4 A recent survey of British general dental practitioners (GDPs) reported that 60% were experiencing symptoms of stress. 5 Occupational burnout may develop in response to prolonged chronic and interpersonal stressors in the work environment 6 and is associated with high levels of exhaustion, cynicism (depersonalisation) and ineffi ciency (reduced personal accomplishment). Schaufeli and Enzmann 7 defi ne burnout as '…a persistent, negative, work related state of mind in "normal" individuals which is primarily characterised by exhaustion, which is accompanied by distress, a sense of reduced effectiveness, decreased motivation, and the development of dysfunctional attitudes and behaviours at work.…”
Section: Verifiable Cpd Papermentioning
confidence: 99%
“…Various organizational and individual stress factors at dental school, in clinical practice building up all the way through, are responsible for professional burnout [1][2][3]. Burnout is a persistent, negative work-related state of mind in "normal" individuals, primarily characterized by emotional exhaustion and accompanied by distress, a sense of reduced effectiveness, decreased motivation, and the development of dysfunctional attitudes and behaviors at work [4]. Burnout leads to negative outcome on quality of work, affecting both professional and personal interests of a dentist.…”
Section: Introductionmentioning
confidence: 99%